The art of ideas : creative thinking for work and life - Duggan, William; Murphy, Amy (Amy Berth), 1984-; Dabalsa, Laura (New York : Columbia Business School Publishing, 2020)
Great ideas don't just happen. Innovation springs from creative thinking--a method of the human mind that we can study and learn. In The Art of Ideas, William Duggan and Amy Murphy bring together business concepts with stories of creativity in art, politics, and history to provide a visual and accessible guide to the art and science of new and useful ideas.In chapters accompanied by charming and inviting illustrations, Duggan and Murphy detail how to spark your own ideas and what to do while waiting for inspiration to strike. They show that regardless of the field, innovations happen in the same way: examples from history, presence of mind, creative combination, and resolution to action. The Art of Ideas features case studies and exercises that explain how to break down problems, search for precedents, and creatively combine past models to form new ideas. It showcases how Picasso developed his painting style, how Gandhi became the man we know today, and how Netflix came to disrupt the movie-rental business. Lavishly illustrated in an appealing artistic style, The Art of Ideas helps readers unlock the secret to creativity in business and in life.
On-line resource; title from PDF title page (EBSCO, viewed October 30, 2019)
Master record variable field(s) change: 072
Keywords: Creative ability in business; Success in business; BUSINESS & ECONOMICS / Decision-Making & Problem Solving; Electronic books